2018
DOI: 10.3390/nu10091271
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Vitamin A Deficiency and Associated Factors in Pregnant Women Receiving Prenatal Care at a Reference Maternity Hospital in Northeastern Brazil

Abstract: Vitamin A is essential for mother and child; however, vitamin A deficiency (VAD) remains a public health issue in various countries, affecting around 19 million pregnant women. In Brazil, the scarcity and inconsistency of data have prevented the prevalence and epidemiological status of VAD from being established. This study aimed to analyze vitamin A nutritional status in women receiving prenatal care at a reference center in northeastern Brazil. A cross-sectional study was conducted with a sample of 676 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…Previous publications reporting a prevalence of 5.2% [59] and 6.2% [81] for serum retinol levels below 0.70 µmol/L may suggest that VAD in pregnant women could finally be close to coming within epidemiological control. Although this is a promising prospect, in view of its importance in decision-making with regard to the readjustment of policies and management of programs on the issue, it should be re-evaluated in new assessments conducted in accordance with WHO and BRINDA recommendations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous publications reporting a prevalence of 5.2% [59] and 6.2% [81] for serum retinol levels below 0.70 µmol/L may suggest that VAD in pregnant women could finally be close to coming within epidemiological control. Although this is a promising prospect, in view of its importance in decision-making with regard to the readjustment of policies and management of programs on the issue, it should be re-evaluated in new assessments conducted in accordance with WHO and BRINDA recommendations.…”
Section: Discussionmentioning
confidence: 98%
“…Serum retinol had no statistically significant effect on the infectious process evaluated by CRP; therefore, it was impossible to adjust for inflammation. In view of these findings, further studies should be conducted to evaluate inflammatory markers in accordance with the recommendations of the WHO and of BRINDA [81].…”
Section: Vitamin a Deficiency During Pregnancy: Epidemiological Asmentioning
confidence: 99%
“…In a study from rural Nepal, a positive effect on pulmonary function was observed in the offspring at the age of 9–13 years, in those whose mothers received supplements with preformed vitamin A during pregnancy. In children whose mothers were supplemented with beta-carotene, no beneficial effects on pulmonary function were observed [51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…[7] Agne and al [8], found a prevalence of 15.2% among children aged 6-23 months. This prevalence was 6.2% in pregnant women (serum retinol level <35 μg / dl or <0.7 μmol / L) [9].…”
Section: Introductionmentioning
confidence: 90%